Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(tana-cota=2\sqrt{3}\Rightarrow\left(tana-cota\right)^2=12\)
\(\Rightarrow\left(tana+cota\right)^2-4=12\Rightarrow\left(tana+cota\right)^2=16\)
\(\Rightarrow P=4\)
\(sinx+cosx=\dfrac{1}{5}\Rightarrow\left(sinx+cosx\right)^2=\dfrac{1}{25}\)
\(\Rightarrow1+2sinx.cosx=\dfrac{1}{25}\Rightarrow sinx.cosx=-\dfrac{12}{25}\)
\(P=\dfrac{sinx}{cosx}+\dfrac{cosx}{sinx}=\dfrac{sin^2x+cos^2x}{sinx.cosx}=\dfrac{1}{sinx.cosx}=\dfrac{1}{-\dfrac{12}{25}}=-\dfrac{25}{12}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: A=(sinx+cosx)^2-1=m^2-1
b: B=căn (sinx+cosx)^2-4sinxcosx=căn m^2-4(m^2-1)=căn -3m^2+4
c: C=(sin^2x+cos^2x)^2-2(sinx*cosx)^2=1-2m^2
![](https://rs.olm.vn/images/avt/0.png?1311)
1: \(sin^6x+cos^6x+3sin^2x\cdot cos^2x\)
\(=\left(sin^2x+cos^2x\right)^2-3\cdot sin^2x\cdot cos^2x\cdot\left(sin^2x+cos^2x\right)+3\cdot sin^2x\cdot cos^2x\)
=1
2: \(sin^4x-cos^4x\)
\(=\left(sin^2x+cos^2x\right)\left(sin^2x-cos^2x\right)\)
\(=1-2\cdot cos^2x\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/
\(\left(\frac{sin2x}{cos2x}-\frac{sinx}{cosx}\right)cos2x=\left(\frac{sin2x.cosx-cos2x.sinx}{cos2x.cosx}\right).cos2x\)
\(=\frac{sin\left(2x-x\right)}{cosx}=\frac{sinx}{cosx}=tanx\)
b/
\(2\left(1-sinx\right)\left(1+cosx\right)=2+2cosx-2sinx-2sinxcosx\)
\(=1+sin^2x+cos^2x-2sinx+2cosx-2sinx.cosx\)
\(=\left(1-sinx+cosx\right)^2\)
c/
\(1+cotx+cot^2x+cot^3x=1+cotx+cot^2x\left(1+cotx\right)\)
\(=\left(1+cotx\right)\left(1+cot^2x\right)=\left(1+\frac{cosx}{sinx}\right)\left(1+\frac{cos^2x}{sin^2x}\right)=\frac{sinx+cosx}{sin^3x}\)
d/
\(\frac{cos3x}{sinx}+\frac{sin3x}{cosx}=\frac{cos3x.cosx+sin3x.sinx}{sinx.cosx}=\frac{cos\left(3x-x\right)}{\frac{1}{2}2sinx.cosx}=\frac{2cos2x}{sin2x}=2cot2x\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1: \(P=sin^22x=1-cos^22x\)
\(=1-\left(cos2x\right)^2\)
\(=1-\left(2cos^2x-1\right)^2\)
\(=1-\left(2\cdot\dfrac{9}{16}-1\right)^2\)
\(=1-\left(\dfrac{9}{8}-1\right)^2=1-\left(\dfrac{1}{8}\right)^2=\dfrac{63}{64}\)
2:
\(cos2x-sin\left(x+\dfrac{\Omega}{3}\right)=0\)
=>\(sin\left(x+\dfrac{\Omega}{3}\right)=cos2x=sin\left(\dfrac{\Omega}{2}-2x\right)\)
=>\(\left[{}\begin{matrix}x+\dfrac{\Omega}{3}=\dfrac{\Omega}{2}-2x+k2\Omega\\x+\dfrac{\Omega}{3}=\Omega-\dfrac{\Omega}{2}+2x+k2\Omega\end{matrix}\right.\)
=>\(\left[{}\begin{matrix}3x=\dfrac{\Omega}{6}+k2\Omega\\-x=\dfrac{1}{6}\Omega+k2\Omega\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{\Omega}{18}+\dfrac{k2\Omega}{3}\\x=-\dfrac{1}{6}\Omega-k2\Omega\end{matrix}\right.\)
\(tan^2x+cot^2x=2=2.tanx.cotx\)
\(\Leftrightarrow tan^2x+cot^2x-2tanx.cotx=0\)
\(\Leftrightarrow\left(tanx-cotx\right)^2=0\Leftrightarrow tanx=cotx=\dfrac{1}{tanx}\)
\(\Leftrightarrow tanx=\pm1\)
\(P=\dfrac{1}{cosx}-\dfrac{cosx}{1+sinx}=\dfrac{1+sinx-cos^2x}{cosx\left(1+sinx\right)}=\dfrac{sin^2x+sinx}{cosx\left(1+sinx\right)}\)
\(=\dfrac{sinx\left(1+sinx\right)}{cosx\left(1+sinx\right)}=tanx=\pm1\)